The Influence of Marketing Communication and Price Perception on Customer Loyalty, with Service Quality as an Intervening Variable, in Tokopedia E-Commerce: A Comparative Study of Millennials and Generation Z - Dika Riva Adhilni; Yanda Bara Kusuma (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study aims to examine the influence of marketing communication and price perception on customer loyalty on the Tokopedia e-commerce platform, considering service quality as an intervening variable. The study also dissects the differences in customer responses based on age groups, specifically millennials and Generation Z. The research method used is a quantitative method with a sample size of 137 respondents. The data collection technique employed is questionnaire distribution. The data analysis technique used is descriptive statistical analysis to describe the relationship between variables. Data analysis was conducted using SPSS version 26, involving several tests such as classical assumption tests, path analysis, T-tests, and determination coefficient tests. The results indicate that marketing communication and price perception, through service quality, do not directly affect customer loyalty, and service quality also does not significantly influence customer loyalty. However, partially, marketing communication and price perception do influence customer loyalty. These findings provide valuable insights into the factors influencing customer loyalty and suggest implications for Tokopedia to pay more attention to its service quality to maintain customer loyalty.